2016
DOI: 10.1108/lht-03-2016-0032
|View full text |Cite
|
Sign up to set email alerts
|

Academic technology confidence levels vs ability in first-year traditional and non-traditional undergraduates

Abstract: Purpose The purpose of this paper is to examine the technology confidence, skills, and post-skills-test emotions in traditional (younger than 24 years old) and non-traditional (24 and older) first-year college students at three undergraduate campuses in the Northeastern USA. Design/methodology/approach Totally, 39 college freshmen from three college campuses were recruited for the study. An online test environment and screen recording software were used to measure student proficiency in using PDFs, Microsoft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Students did improve their confidence in using the tools necessary to compile and organize their data (i.e., Microsoft Excel). Eichelberger and Imler (2016) found that traditional students tend to be more confident in technology skills as compared to non‐traditional students, although they appear to be equivalent in the application of the skills. This suggests the presence of disparities in access to particular tools may be uneven across student populations.…”
Section: Discussionmentioning
confidence: 99%
“…Students did improve their confidence in using the tools necessary to compile and organize their data (i.e., Microsoft Excel). Eichelberger and Imler (2016) found that traditional students tend to be more confident in technology skills as compared to non‐traditional students, although they appear to be equivalent in the application of the skills. This suggests the presence of disparities in access to particular tools may be uneven across student populations.…”
Section: Discussionmentioning
confidence: 99%